Magnetic data analysis using 2D inversion: A case study from Terak Radiogenic Geothermal area, Bangka Island, Indonesia - Siregar, Rahmat Nawi; Rohim, Miftahul; Permanasari, Ikah Ning Prasetiowati; Puspitarum, Deska Lismawenning; Umam, Rofiqul (UNIVERSITAS INDRAPRASTA PGRI, 2025)
The presence of geothermal manifestation such as Terak hot spring near granite massive bodies on Bangka Island raises an importatnt question about the subsurface characteristics of a potential radiogenic system. As traditional geothermal system in Indonesia is well known, research must now focus on understanding the radiogenic system, especially on the subsurface information. This study addresses the local magnetic susceptibility of Terak subsurface hot spring by performing magnetic method. The integration of 2D to 3D magnetic data, field observations and geological information show high susceptibility data (>0.005 SI) which are indicated as granite intrusion which act as the heat source. A central zone of lower susceptibility (<0.005 SI) displays a distinct pattern, interpreted as a fracture zone as the hydrothermal fluid pathways. The identification of recharge area further supports the interpretation of an active hydrothermal system. The result of this study are in good agreement with the geological framework of the region and contribute to a better understanding of radiogenic geothermal systems in Indonesia.